THE SHADOW ECONOMY AS AN ECONOMIC CATEGORY AND OBJECT EVALUATION - А. Khodzhaian; T. Shyptenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article considers the existing scientific approaches to the formulation of the concept of nature and the structural elements of the shadow economy. Contains definitions of the shadow economy as an object of evaluation. Disclosed manifestations shadow relations in the context of the institutional sectors. Characterized by methods of assessment of the informal sector in terms of their object of study.